(untitled) (Swiss Medical Weekly, 2026)
STUDY AIMS: Timely defibrillation is a critical determinant of survival in out-of-hospital cardiac arrests, yet public access to automated external defibrillators (AEDs) remains spatially and temporally uneven, particularly in decentralised health systems. This study aimed to quantify AED accessibility and spatial overcoverage across the urban–rural gradient using high-resolution geospatial data from Switzerland as a model system. METHODS: We conducted a national cross-sectional geospatial analysis using AED locations (n = 14,446) from Defikarte.ch (December 2024), hectare-level population grids from the Federal Statistical Office (2023) and the 9-category municipality typology. The primary outcome was AED accessibility, defined as the proportion of the population within a 300-metre retrieval buffer of a 24-hour-accessible AED. Secondary outcomes included population coverage gain, comparing current 24-hour AED access with a hypothetical scenario in which all AEDs are accessible 24-hours, and spatial overcoverage, defined as overlapping AED buffers, indicating redundancy. Population exposure quantified the share of residents within these zones. Differences across municipality types were tested using the chi-squared test, paired t-test and Kruskal–Wallis test with Dunn’s post-hoc comparison. RESULTS: Expanding all AEDs to 24-hour access significantly increased national coverage from 28.9% to 51.6% (t = 3.96, p <0.005) but failed to resolve persistent deficits in agricultural and tourist communes. Statistical tests confirmed significant variation in accessibility (chi-squared test, p <0.001) and overcoverage (Kruskal–Wallis test, p <0.001) across municipality types. Overcoverage was concentrated in urban cores, while rural areas exhibited predominantly single-device coverage. Population exposure analysis indicated that overlap zones accounted for 28.6% of the covered population and 8.3% of the total population. CONCLUSION: This national analysis identified major spatial and temporal inequities in AED accessibility across Switzerland. Expanding all AEDs to 24-hour availability improves coverage but does not resolve structural gaps, with persistent undercoverage in rural areas and clustering in urban cores. Equitable access will require coordinated planning, mandatory 24-hour availability, and spatial redistribution aligned with population needs.